Baque de caboclo no carnaval de Pernambuco: entre a festa e a vida - Alcântara, Paulo Henrique Lopes de (2020)
Maracatu de baque solto is a cultural expression from the sugarcane region of Pernambuco, and is closely linked to Carnival festivities. This dissertation focuses on maracatu musical agents, their motivations for playing during Carnival, and the ways in which these Carnival experiences can influence their lives. As such, I defend the hypothesis that for the batedores de terno (percussionists) and músicos (brass and woodwind players), these experiences are much more than just a practice; it is a means of momentarily meeting some of their daily expectations and necessities, being part of the process by which they construct and reconstruct their subjectivities.